Nilai Kepahlawanan dalam Cerita Rakyat “Hikayat Datuk Tuan Budian” karya Susilowati, dan “Sultan Domas Pemimpin yang Sakti dan Baik Hati” karya Yuli Nugrahani: Values of Heroism in Susilowati’s Hikayat Datuk Tuan Budian and Yuli Nugrahani’s Sultan Domas Pemimpin yang Sakti dan Baik Hati - Erwin Wibowo (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This study aims to describe the heroic values contained in folktale books.The method used in this research is descriptive data in the form of words which quotations. Source folktale is the book entitled “Hikayat Datuk Tuan Budian”, and “Sultan Domas Pemimpin yang Sakti dan Baik Hati” published by the Lampung Language Office in 2017. Results from this study is that there are values of heroism in the two books of folktale.Heroic values that may include sacrifice, ideals, values loyalty, the value of humility and responsibility.